Peran Teknologi Informasi Dalam Meningkatkan Korespondensi Sekolah di MAS PAB 1 Sampali - Indri Febrianti; Winda Aidin; Melin Andila; M. Faqih Abdillah Harahap; Tengku Darmansah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to investigate the role of information technology in enhancing school correspondence at MAS PAB 1 Sampali. The introduction of the research explains the importance of using information technology to improve communication effectiveness in the educational environment. The research method used is qualitative with a literature review approach, involving analysis of various related literature. The research objectives are to understand the implementation of digital platforms in school correspondence, the impact of information technology on interaction and social relations in schools, and enhancing communication effectiveness among schools. The research findings indicate that digital platforms have had a positive impact in facilitating online learning, expanding communication networks among students, teachers, and parents, and increasing engagement in school life. However, the use of technology also brings challenges related to privacy and data security that must be addressed with appropriate policies and security measures. In conclusion, information technology has great potential to enhance school communication effectiveness, but its use must be managed wisely to ensure data security and privacy are maintained.